Substance abuse and intimate partner violence: treatment considerations - Klostermann Keith C (BMC, 2006)
Abstract Given the increased use of marital- and family-based treatments as part of treatment for alcoholism and other drug disorders, providers are increasingly faced with the challenge of addressing intimate partner violence among their patients and their intimate partners. Yet, effective options for clinicians who confront this issue are extremely limited. While the typical response of providers is to refer these cases to some form of batterers' treatment, three fundamental concerns make this strategy problematic: (1) most of the agencies that provide batterers' treatment only accept individuals who are legally mandated to complete their programs; (2) among programs that do accept nonmandated patients, most substance-abusing patients do not accept such referrals or drop out early in the treatment process; and (3) available evidence suggests these programs may not be effective in reducing intimate partner violence. Given these very significant concerns with the current referral approach, coupled with the high incidence of IPV among individuals entering substance abuse treatment, providers need to develop strategies for addressing IPV that can be incorporated and integrated into their base intervention packages.